(untitled) (Texas Journal of Engineering and Technology, 2026)
This article presents the assessment of the seismic resistance level of reservoirs used in the oil and oil-gas industry and examines the conditions required to maintain their structural stability under dynamic loading. The study includes the analysis of existing operating reservoirs using the LIRA-SAPR 10.12 software package, with particular emphasis on the evaluation of equivalent stress results. Furthermore, the distribution of equivalent stresses occurring in the plates of a cylindrical steel reservoir structure was analyzed based on calculation results obtained for liquid filling levels of 50%, 75%, and 100%.